She just did: a narrative case study of black women student leaders at a predominantly white midwestern institution - Lander, Teara Flagg (Kansas State University, 2017)
The purpose of this narrative case study was to explore the lived experiences of four Black undergraduate collegiate women leaders in higher education in their third and fourth years of study in a predominantly White Midwestern institution. This qualitative study was conducted with purposeful and criterion-based sampling. The participants selected needed to be at least a student leader in a registered student organization at one time during their collegiate career. Narrative inquiry was used to explore the participants’ racialized, gendered, and leadership identity development prior to college and throughout the course of their collegiate careers. The participants’ narratives were organized using Bildungsroman format, or as a coming of age story. Findings indicate that although the participants identified as Black women and Black women student leaders, their racialized identity was much more salient than their gendered identity. Therefore, outside of biological markers like menstruating and becoming mothers, they were not able to articulate the development of their intersectional identity. Findings also show the participants had a certain amount of self-confidence and critical self-awareness that allowed them to succeed even when faced with racialized and gendered discrimination as individuals and within their roles as student leaders. Such obstacles contributed to their ability to just do when faced with challenges regardless of the difficulty level of the challenge. The study raises implications about the multitude of support systems that Black women and girls have upon entering college. Another implication is the amount of invisible labor that Black women as collegiate leaders do in order to support their fellow peers. Finally, this study raises implications about the deficit narratives that depict Black women’s and girls’ stories within education. Thus, this study presented a counternarrative to the traditional, negative, and stereotypical narratives that are untrue and detrimental to the racialized, gendered, and leadership development of Black women and girls within and beyond the education system.
Keywords: Women; Leadership; Black feminist; IntersectionalityBlack